TERPSTRA, Nicholas (2019), Lives Uncovered: A Sourcebook of Early Modern Europe, University of Toronto Press. ISBN: 978-144-26-0732-3, 304 pp. - Pinto, Sara (História: revista da Faculdade de Letras da Universidade do Porto, 2022)
TERPSTRA, Nicholas (2019), Lives Uncovered: A Sourcebook of Early Modern Europe, University of Toronto Press. ISBN 978-144-26-0732-3, 304 pp.